Avaliação do óleo de coco extravirgem no controle da adiposidade e suas comorbidades. - Marina Campos Zicker (2016)
The obesity is characterized by excessive fat storage and since it is associated with chronic low grade inflammation and significant oxidative stress, this disease is involved in triggering metabolic and bone disorders. Studies have shown that certain foods could promote beneficial effects in obesity and related comorbidities, once they induce lower weight gain, decrease of inflammation and higher oxidative defense. Among those foods, despite low scientific evidence, we can mention virgin coconut oil (VCO). Health benefits have been attributed to VCO consumption that may be related to the content of bioactive ingredients such as polyphenols, vitamins and medium chain fatty acids (MCFA), lipids that could act to decrease adiposity gain and to promote metabolic homeostasis. The aim of the present study was to investigate the physical and chemical properties of VCO, evaluating their quality and identity, and thus, analyzing the potential in treating obesity and related metabolic, inflammatory and bone disorders, induced by a highrefined carbohydrate-containing diet in mice. The VCO supplementation induced lower adiposity associated with lower adipocyte area, due to acetyl coa carboxylase lower expression. The VCO consumption has also promoted maintenance of glycemic homeostasis, lower serum concentration of lipids (cholesterol and triglycerides), non-esterified fatty acids and leptin, higher adiponectin serum concentration, decrease of total lipids and cholesterol in liver, lower leukocytes rolling in epididymal adipose tissue, lower concentration of proinflammatory cytokines (IL-6 e TNF-α) in epididymal and inguinal adipose tissues, as well as lower blood count of total leukocytes, mononuclear and polymorphonuclear cells. Animals that were fed with VCO also exhibited greater percentage of trabecular bone in different bone sites (tibia, femur, lumbar vertebrae and maxillae) in addition to higher femur and alveolar bone mineral density. In conclusion, VCO supplementation was effective to control obesity and related metabolic, inflammatory and bone disorders in experimental obesity model.